Magnetosomes, Biogenic Magnetic Nanomaterials for Brain Molecular Imaging with 17.2 T MRI Scanner. Issue 7 (13th February 2015) - Mériaux, Sébastien; Boucher, Marianne; Marty, Benjamin; Lalatonne, Yoann; Prévéral, Sandra; Motte, Laurence; Lefèvre, Christopher T.; Geffroy, Françoise; Lethimonnier, Franck; Péan, Michel; Garcia, Daniel; Adryanczyk‐Perrier, Géraldine; et al.
<x xml:space="preserve">Abstract</x> The fast development of sensitive molecular diagnostic tools is currently paving the way for a personalized medicine. A new class of ultrasensitive magnetic resonance imaging (MRI) T2‐contrast agents based on magnetosomes, magnetite nanocrystals biomineralized by magnetotactic bacteria, is proposed here. The contrast agents can be injected into the blood circulation and detected in the picomolar range. Purified magnetosomes are water‐dispersible and stable within physiological conditions and exhibit at 17.2 T a transverse relaxivity r2 four times higher than commercial ferumoxide. The subsequent gain in sensitivity by T2*‐weighted imaging at 17.2 T of the mouse brain vasculature is evidenced in vivo after tail vein injection of magnetosomes representing a low dose of iron (20 μmoliron kg−1), whereas no such phenomenon with the same dose of ferumoxide is observed. Preclinical studies of human pathologies in animal models will benefit from the combination of high magnetic field MRI with sensitive, low dose, easy‐to‐produce biocompatible contrast agents derived from bacterial magnetosomes.